Improved pentacene device characteristics with sol–gel SiO2 dielectric films - Cahyadi, Tommy (2013)
The interfacial interactions between semiconductors and gate dielectrics have a profound influence on the device characteristics of field effect transistors (FETs). This paper reports on the concept of introducing a sol–gel SiO2 as inorganic capping layer to significantly improve device characteristics of pentacene-based FETs. The smoother film surfaces of sol–gel SiO2 (1.9 Å root-mean-square) induced larger pentacene grain sizes, and led to hole mobilities of 1.43 cm2/Vs, on–off ratio of 107, and a subthreshold swing of 102 mV/decade when operating at −20 V.